Taxation and Tax Farming in the Egibi Archive - Wang, Jinyan (2023)
The Egibi archive contains a group of texts concerning the tax farming activities of Marduk-nāṣir-apli, son of Itti-Marduk-balāṭu, the head of the Egibi family in the third generation (521-487 BCE). This group of texts includes documents that refer to various taxes, such as ilku and qaštu , mostly in the form of receipts, as well as a dossier of a rab hanše , Bēl-erība, son of Kalbāya, descendant of Šumu-libši, who was closely involved in the collection of ilku . A detailed analysis and contextualization of these texts reveal the ilku taxation processes, and the roles of the rab hanšê Bēl-erība and the tax farmer Marduk-nāṣir-apli in these processes. These texts also add more evidence for the taxation on the military fiefs and qaštu -tax in Babylon.
Keywords: Egibi; tax farming; Taxation